Including Sustainable Architectural Design in the Teaching Pedagogy: A District Adapted to the Desert Climate of the Oasis of Nafta–Tunisia - Jouini, Nour El Houda; Kharrat, Fakher; Chaabani, Mouldi; Zair, Kaouther (2022)
Nafta is an oasis located in the governorate of Tozeur in the South of Tunisia. The unique natural and built environment it offers has been degrading due to climate change, pollution, and overexploitation. Additionally, the new residential districts are unsuitable for the desert climate of the area. Not only do they fail to provide thermal comfort, especially during the heat waves, but also they contain non-eco-friendly materials such as concrete. However, we notice that the vernacular architecture respects the climate context and can serve as a reference. Teaching second-grade architecture students, we tried to include this in our pedagogy method to raise awareness about the matter. This paper presents the project of a sustainable district in Nafta conducted with the students during a workshop. The study shows that urban morphology and the building design can significantly influence the energy efficiency and the ecological footprint of the district. It also reveals that the vernacular architecture can be a reference to rebuilt contemporary eco-friendly cities.
Keywords: C:Tunisia; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:sustainable architectural design; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:n:1; openalex:yes